POLITIK HUKUM PELEMBAGAAN KOMISI-KOMISI NEGARA DALAM SISTEM KETATANEGARAAN INDONESIA - Alamsyah, Bunyamin; Huda, Uu Nurul (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
During the 32 years of the New Order government certainly has its advantages and disadvantages, in terms of the development of infrastructure and supra-structure growing rapidly, but the journey has decreased function of government and its role even stagnant. Therefore, there was the Reform of 1998 in a variety of fields. In reply funsgi decline and the role of government under the Constitution of 1945, there was an opinion with the formation of a new organization outside the government. Gagsan ideas are realized with the establishment of committees that do not require the State budget a little, sometimes a clash of authority between committees also with government agencies. Committees should not be separated from the politics of law. Keywords: Institutionalization of Political Law, Commissions of the State, State Administration System